2017
DOI: 10.1111/rego.12172
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarian but responsive:Local regulation of industrial energy efficiency inJiangsu,China

Abstract: Regulatory behavior and effectiveness in authoritarian settings are subject to alternative characterizations. By tracing enforcement processes through a variety of case studies, this article proposes and refines a new model, at least with respect to energy efficiency regulations in China: authoritarian but responsive. Local rulemaking and operationalization is authoritarian, with strong and coordinative bodies of regulation, strategic plans, and active involvement of local authorities. Local authorities, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
(112 reference statements)
1
5
0
Order By: Relevance
“…Local governments are responsible for local development and environmental protection. They should respond to the performance and demands of regulated firms [ 124 ]. They may hope polluters to bring economic development and help local governments improve indicators of economic development such as investments, GDP, employment, and taxes.…”
Section: Discussionmentioning
confidence: 99%
“…Local governments are responsible for local development and environmental protection. They should respond to the performance and demands of regulated firms [ 124 ]. They may hope polluters to bring economic development and help local governments improve indicators of economic development such as investments, GDP, employment, and taxes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, scholars have mapped examples of alternative applications of responsive regulation. For example, Zhu and Chertow (2019) observed that local regulators in Jiangsu Province (China) set out to enforce a newly introduced energy efficiency regulation in a formal and coercive manner before switching to a more accommodative manner. This “inverse” enforcement pyramid illustrates that the responsive regulation theory is somewhat pliable, and that some care is warranted when drawing lessons from such studies.…”
Section: Resultsmentioning
confidence: 99%
“…The positive performance reported ranged from being substantial (e.g. increased tax revenue for the Florida Department of Revenue (Christian 2017); increased energy savings by Chinese firms (Zhu & Chertow 2019) to being only modestly better (e.g. increased compliance with human rights standards by global garment manufacturers (Islam & McPhail 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations